Anthropological Interpretation of the Meaning of Ritual Objects in the Contemporary Urban Wedding in Bulgaria - Rozaliya Guigova (Journal of Ethnology and Folkloristics)
This paper discusses the changing symbolic potential of items in the Bulgarian contemporary urban wedding. Based on my fieldwork material regarding the wedding cake and other items, I investigate cultural change in modern Bulgarian society not only as a result of the one-way process of transference, adaptation and incorporation of mass produced commodities into Bulgarian culture but also as a process of cultural change and variation. In that sense, I investigate the alternation between global and local perspectives of the forms of material culture in which certain levels of meaning, inherent to objects, play a crucial role, as for example the social communication factor, kinship ties, cross-generational continuity, local ritual and symbolic systems, local food culture, and even the personal fate and private life of an object’s owner. In this article I focus mainly on the wedding cake as a specific ritual item, functioning in the contemporary urban Bulgarian wedding, transmitted during the last decades from West European culture into the Bulgarian wedding tradition, and analyse the specific dialogue between ‘global’ items and local culture. Furthermore, taking as my example the wedding cake and other ritual objects (the wedding chicken, the wedding bread, and the sponsor’s stick) I question the concept of the globalisation, homogenisation and unification of forms of material culture in contemporary society.